Neuroprotective Effect of Artichoke-Based Nanoformulation in Sporadic Alzheimer's Disease Mouse Model: Focus on Antioxidant, Anti-Inflammatory, and Amyloidogenic Pathways - Heba A. S. El-Nashar; Haidy Abbas; Mariam Zewail; Mohamed H. Noureldin; Mai M. Ali; Marium M. Shamaa; Mohamed A. Khattab; Nehal Ibrahim (MDPI AG, 2022)
The vast socio-economic impact of Alzheimer's disease (AD) has prompted the search for new neuroprotective agents with good tolerability and safety profile. With its outstanding role as antioxidant and anti-inflammatory, alongside its anti-acetylcholinesterase activity, the artichoke can be implemented in a multi-targeted approach in AD therapy. Moreover, artichoke agricultural wastes can represent according to the current United Nations Sustainable Development goals an opportunity to produce medicinally valuable phenolic-rich extracts. In this context, the UPLC-ESI-MS/MS phytochemical characterization of artichoke bracts extract revealed the presence of mono- and di-caffeoylquinic acids and apigenin, luteolin, and kaempferol O-glycosides with remarkable total phenolics and flavonoids contents. A broad antioxidant spectrum was established in vitro. Artichoke-loaded, chitosan-coated, solid lipid nanoparticles (SLNs) were prepared and characterized for their size, zeta potential, morphology, entrapment efficiency, release, and ex vivo permeation and showed suitable colloidal characteristics, a controlled release profile, and promising ex vivo permeation, indicating possibly better physicochemical and biopharmaceutical parameters than free artichoke extract. The anti-Alzheimer potential of the extract and prepared SLNs was assessed in vivo in streptozotocin-induced sporadic Alzheimer mice. A great improvement in cognitive functions and spatial memory recovery, in addition to a marked reduction of the inflammatory biomarker TNF-α, β-amyloid, and tau protein levels, were observed. Significant neuroprotective efficacy in dentate Gyrus sub-regions was achieved in mice treated with free artichoke extract and to a significantly higher extent with artichoke-loaded SLNs. The results clarify the strong potential of artichoke bracts extract as a botanical anti-AD drug and will contribute to altering the future medicinal outlook of artichoke bracts previously regarded as agro-industrial waste.